The Role of Context Intensity and Working Memory Capacity in the Consumer's Processing of Brand Information in Entertainment Media. Issue 7 (8th June 2015) - Rumpf, Christopher; Noël, Benjamin; Breuer, Christoph; Memmert, Daniel
ABSTRACT: Despite the increasing use of entertainment media such as movies, sport telecasts, or video games as a way to get in touch with consumers, the understanding of the cognitive processing of brand information in these environments is still limited. This current research investigates the role of two moderating factors on brand information processing in entertainment media: Context intensity and working memory capacity. Context intensity relates to the perceived level of excitement in a communication environment, while working memory capacity indicates a consumer's ability to control his or her cognitive resources. The results of an experimental laboratory study reveal that context intensity negatively affects visual attention for brand information (i.e., intensity attention assumption), while working memory capacity has a positive influence on memory for brands (i.e., capacity memory assumption). These findings hold important implications for marketing management: First, managers should place brand information in situations where context intensity is rather low in order to facilitate the target group's visual attention. Second, the frequency and duration of brand information should be adjusted to the target group's ability to cognitively process such information.